Tentativas de paz na Guerra do Paraguai - Francisco Doratioto (Navigator)
This article analyzes three attempts to reach an armistice during the Paraguay War in order to bring the Parties in the dispute to negotiate peace. Two of these attempts – from United States and South American republics – were intentional and one resulted from the existing circumstances. All of these attempts have failed, either because they happened when Francisco Solano López had positive expectations regarding the war, or because to the Brazilian Empire only victory could guarantee the Monarchic State’s objectives not to be jeopardized.